Diversidade genética de Schizolobium parahyba var. amazonicum (Huber ex. Ducke) Barneby, em área de plantio no Espírito Santo - Silva Júnior, Adelson Lemes da (2016)
Schizolobium parahyba var. amazonicum (Huber ex. Ducke) Barneby, is popularly known as Paricá and endemic to the Amazon rainforest. Its wood is of great acceptance in the timber sector, due to its well formed and straight trunk, with smooth, uniform texture and sapwood white. It also presents ecological importance and may be used in degraded areas restoration projects due to its rapid growth. For landscaping is considered an ornamental species, because of its intense yellow flowering, sweet aroma. However, despite the importance and potential of the species, there is no availability of genetically improved material, selected to the environmental conditions of the Espírito Santo. In this sense, the present study aimed to characterize the genetic diversity in a population of S. amazonicum established in an area of forest planted in the southern state of Espírito Santo. Information on the population structure and genetic diversity are needed in pre-breeding program and germplasm conservation of this species, especially when you want to use this as planting seed orchard. The experimental design was randomized blocks, consisting of 3 blocks and 5 treatments, ie five spacings (3x2 m, 3x3 m, 3x4 m, 4x4 m and 5x5 m). Initially, it carried out the forest inventory of the population for the variables dendrometric diameter at breast height (DBH) and total height (Ht). Analysis of variance and the Tukey test revealed that only the treatments had an effect on dendrometric variables. Therefore, they were chosen that had higher average and were not statistically different from each other, and the treatments T3, T4 and T5 representing the spacing 3x4 m, 4x4 m and 5x5 m, respectively. Thus, for the selection of mother trees was carried out the overall average of DAP and Ht variables for the chosen treatments, being marked and georeferenced 57 trees in each treatment, totaling 171 trees. For the purpose of the study were used 11 primers Inter Simple Sequence Repeats (ISSR), which generated 79 polymorphic (58%). About polymorphic information content (PIC) held for ISSR, average of 0.37 was found, characterizing them as informative averagely. The locos number found (n = 79) was higher than that established as optimal number (n = 69). The results corroborated the dendrogram with Bayesian analysis by STRUCTURE program, according to the method ?K the most likely number of clusters K is defined as two (K = 2). Thus, a group formed with the majority of individuals (genotypes 153) and the second with a minority (18 genotypes). High genetic diversity was found with number of observed alleles (Na = 2.00), number of effective alleles (Ne = 1.65), diversity index of Nei (H' = 0.375) and Shannon index (I = 0.554). With this study we found that the ISSR markers were efficient to characterize the genetic diversity in S. amazonicum, and that the population can be used as orchard for seed collection and seedling production with greater genetic variability.